IDENTIFICATION OF THE CAUSES NATA DE COCO PRODUCTION DEFECTS FOR QUALITY CONTROL - Mahmud Basuki; Rizqa Ula Fahadha (Universitas Ahmad Dahlan Indonesia, 2020)
Nata de coco is food made from coconut water waste which can be consumed and can help improve the digestive process. The results of fermentation at PT XYZ still contain damaged or moldy nata sheets. The purpose of this study is to identify the causes of nata sheet defects. The identification of production defects in this study uses a fishbone diagram. The results of this study show that the cause of nata de coco sheet defects is the quality of coconut water that is too old (contains oil), too young (does not contain minerals), too long exposure to open air (contaminated with other bacteria). So that the resulting starter seeds are not good enough. Other causes are because the tray used is not clean (still runny), the newspaper used is torn (wide open), shocks occur during fermentation, alkaline pH, fluctuating air temperature, the boiling process has not reached boiling point, and the amount of additional materials (ZA fertilizer and sugar) is not quite right.